Molecular phylogeny of Toxoplasmatinae: comparison between inferences based on mitochondrial and apicoplast genetic sequences - Sercundes,Michelle Klein (2016)
Abstract Phylogenies within Toxoplasmatinae have been widely investigated with different molecular markers. Here, we studied molecular phylogenies of the Toxoplasmatinae subfamily based on apicoplast and mitochondrial genes. Partial sequences of apicoplast genes coding for caseinolytic protease (clpC) and beta subunit of RNA polymerase (rpoB), and mitochondrial gene coding for cytochrome B (cytB) were analyzed. Laboratory-adapted strains of the closely related parasites Sarcocystis falcatula and Sarcocystis neurona were investigated, along with Neospora caninum, Neospora hughesi, Toxoplasma gondii (strains RH, CTG and PTG), Besnoitia akodoni, Hammondia hammondiand two genetically divergent lineages of Hammondia heydorni. The molecular analysis based on organellar genes did not clearly differentiate between N. caninum and N. hughesi, but the two lineages of H. heydorni were confirmed. Slight differences between the strains of S. falcatula and S. neurona were encountered in all markers. In conclusion, congruent phylogenies were inferred from the three different genes and they might be used for screening undescribed sarcocystid parasites in order to ascertain their phylogenetic relationships with organisms of the family Sarcocystidae. The evolutionary studies based on organelar genes confirm that the genusHammondia is paraphyletic. The primers used for amplification of clpC and rpoB were able to amplify genetic sequences of organisms of the genus Sarcocystisand organisms of the subfamily Toxoplasmatinae as well.